Perlindungan Hukum Bagi Konsumen Muslim Terhadap Peredaran Makanan Tidak Bersertifikat Halal (Studi pada LPPOM MUI Sumatera Utara di Medan - Masnun Nasution (Jurnal Hukum Kaidah: Media Komunikasi dan Informasi Hukum dan Masyarakat, 2020)
The regulations for legal protection for Muslim consumers against the circulation of not halal food certified are regulated in the Law of the Republic of Indonesia Number 18 of 2012 concerning Food and the Law of the Republic of Indonesia Number 8 of 1999 concerning Consumer Protection, the Law of the Republic of Indonesia Number 33 of 2014 concerning Halal Product Guarantee. The role of LPPOM MUI in halal certification is as LPH where LPPOM will be an institution that carries out the process of inspecting food ingredients, inspecting product processing, examining equipment, production rooms, and checking the halal assurance system. In addition, the role of LPPOM MUI as LPH is to submit the results of the inspection and / or testing the halalness of the product to BPJH. Keywords: Legal Protection, Muslim Consumers, Food Circulation, Not Halal Certified.